Presence of estrogen and progesterone receptors in proliferating and involuting infantile hemangiomas. Issue 11 (November 2021) - Johnson, Adam; Zhang, Haihong; Gonzalez, Santiago R.; Lee, Madison; Wei, Ting; Richter, Gresham
Summary: Background: Studies in the literature have demonstrated the presence of sex hormone receptors in infantile hemangiomas (IHs), but further investigation is needed to determine the role of these receptors in their proliferation and involution. To date, there are no studies in the literature that aimed to quantitatively examine the expression of sex hormone receptors throughout the different phases of hemangioma development. Objective: The objective of our study was to quantitatively evaluate the expression of estrogen (ER) and progesterone (PR) receptors in the proliferative and involuting phases of IHs through the use of real-time polymerase chain reaction (RT-PCR). Methods: Twenty IHs (10 proliferating and 10 involuting) were harvested and prepared for molecular investigation. ER receptor alpha (ERα) and beta (ERβ) and the PR expression were examined by RT-PCR and western blot. Results: RT-PCR analysis demonstrated that mRNA expression of ERα, ERβ, and PR was significantly lower in proliferating versus involuting IH. Western blot analysis revealed increased protein expression of ERα in involuting hemangiomas as compared to proliferating ones. Conclusions: Our study demonstrates the variable expression of ER and PR receptors in proliferating and involuting hemangiomas. Further studies are needed to determine the exact role of these hormone receptors in the growth and involution of IHs.